PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA EDUKASI HUKUM: STUDI KASUS AKUN INSTAGRAM SPRIPIM POLDA JATIM (@spripimpoldajatim) - Febriyanu, Baskara; Marwiyah, Siti; Astutik, Sri; Subekti, Subekti (Gapenas Publisher, 2025)
The level of legal literacy among Indonesians is still relatively low, requiring more effective educational strategies that are closely related to everyday life. In the digital age, social media has become a communication channel that can reach a wide audience quickly, interactively, and participatively. One initiative that has been undertaken is the use of the Instagram account @spripimpoldajatim by the East Java Regional Police as a means of legal education. The urgency of this research lies in the importance of understanding the effectiveness of police social media in increasing public legal awareness. The main questions of this research are how the account is used as an instrument of legal education, what types of content are used, and to what extent it is effective in building public legal literacy. This study uses a descriptive qualitative approach with a combination of sociological and juridical perspectives. Data were collected through observation of the Instagram account content, interviews with account managers and active followers, documentation of uploaded archives, and literature studies. Data validity was strengthened through source triangulation, while data analysis was conducted using inductive, deductive, and comparative methods. The results show that @spripimpoldajatim actively presents legal education content in the form of infographics, short videos, and narratives of actual cases with a humanistic communication style. Visual and narrative strategies have been proven to increase public interaction, as evidenced by the high number of likes, comments, and shares. Content based on current issues and storytelling is the most effective format for attracting audience attention. These findings confirm that police social media can be an instrument of participatory digital legal literacy, although there are still limitations in reaching non-digital communities and risks of misperceptions of information. The conclusion of the study emphasises that the use of social media by the police contributes theoretically to the development of digital legal communication studies and provides practical benefits for legal education strategies in the information age. Further research using a mixed-method approach and comparisons between police accounts is recommended to strengthen the generalisation of the results.